Proton range verification with ultrasound imaging using injectable radiation sensitive nanodroplets: a feasibility study. (23rd March 2020) - Carlier, Bram; Heymans, Sophie V; Nooijens, Sjoerd; Toumia, Yosra; Ingram, Marcus; Paradossi, Gaio; D'Agostino, Emiliano; Himmelreich, Uwe; D'hooge, Jan; Van Den Abeele, Koen; Sterpin, Edmond
Abstract: Technologies enabling in vivo range verification during proton therapy are actively sought as a means to reduce the clinical safety margins currently adopted to avoid tumor underdosage. In this contribution, we applied the semi-empirical theory of radiation-induced vaporization of superheated liquids to coated nanodroplets. Nanodroplets are injectable phase-change contrast agents that can vaporize into highly echogenic microbubbles to provide contrast in ultrasound images. We exposed nanodroplet dispersions in aqueous phantoms to monoenergetic proton beams of varying energies and doses. Ultrasound imaging of the phantoms revealed that radiation-induced droplet vaporization occurred in regions proximal to the proton Bragg peak. A statistically significant increase in contrast was observed in irradiated regions for doses as low as 2 Gy and found to be proportional to the proton fluence. The absence of enhanced response in the vicinity of the Bragg peak, combined with theoretical considerations, suggest that droplet vaporization is induced by high linear energy transfer (LET) recoil ions produced by nuclear reactions with incoming protons. Vaporization profiles were compared to non-elastic cross sections and LET characteristics of oxygen recoils. Shifts between the ultrasound image contrast drop and the expected proton range showed a sub-millimeter reproducibility. These early findings confirm the potential of superheated nanodroplets as a novel tool for proton range verification.